OPTIMIZATION OF TEACHING STRATEGIES OF TAHFIDZ TEACHERS TO IMPROVE THE QUALITY AND QUANTITY OF STUDENT'S MEMORIZATION OF THE QUR'AN - Tutik Rahayu; Joko Subando; Meti Fatimah; Arafiq Fathul Haq Rumaf; Abdul Kabir Hussain Solihu (Profetika: Jurnal Studi Islam, 2023)
This study aims to determine the Learning Strategies of Tahfidz Teachers in Efforts to Increase Al-Qur'an Memorization. This research method uses a qualitative approach. Meanwhile, the subject of this research was SDIT Muhammadiyah Al-Kautsar Gumpang Kartasura. Collecting data in this study by participant observation, in-depth interviews and documentation. While the data analysis uses data reduction, the presentation of the data then concludes. The results of this study indicate that: (1) The strategy used by the teacher in increasing students' memorization of the Qur'an at SDIT Muhammadiyah Al-Kautsar Gumpang Kartasura is using the strategy of grouping students in large, classical and individual classes, the Al-Qur'an memorization method using the talaqqi, murajaah and tasmi' methods while the evaluation of memorization is by deposit method which is monitored by a memorization achievement book. 2) Factors that influence the implementation of improving students' memorization of the Al-Qur'an at SDIT Muhammadiyah Al-Kautsar Gumpang Kartasura include supporting factors, namely: age factor, student intelligence, Al-Qur'an memorization achievement books, supporting infrastructure and motivation parent. The inhibiting factors are: often making noise, not focusing on memorization, the appearance of laziness, and lack of attention from parents. (3) The implications of implementing the strategy used by the teacher in increasing the memorization of the Qur'an at SDIT Muhammadiyah Al-Kautsar Gumpang Kartasura, namely: students are more enthusiastic and able to memorize the Qur'an according to the target